Attitude of the Chronic Kidney Disease Patients Toward Xenotransplantation of Organs. (July 2018) - Balwani, Manish; Pasari, Amit; Aziz, Feroz; Ookalkar, Dhananjay; Patel, Mohan; Kute, Vivek; Shah, Pankaj
Abstract : Background: Although xenotransplantation is still in an experimental phase, it is presented herein as a possible solution to the organ shortage. However, there are scarce data concerning how the chronic kidney disease patients would accept treatment with animal organs especially more so now in the wake of animal disease transmission in human beings. The aim of this study was to determine the attitude of the chronic kidney disease patients toward xenotransplantation of organs. Materials and Methods: Using an opinion survey, a study was performed on a random sample of 120 subjects in an single center out of which 100 completed the survey successfully. The questionnaire was administered by personnel from the dialysis center. Completion of the form was self-directed and anonymous for each respondent. The attitude toward donation of human and animal organs was evaluated by analyzing different psychosocial variables that may influence this attitude. A descriptive statistical study was performed. Results: As for human donation, 90% are in favor of cadaveric donation. 88 out of 100 patients never heard of the term xenotransplantation. As for animal donation, if the results were similar to those obtained with human organs, 80% (n=27) would accept an animal organ as opposed to 20% who were against. Given, if the results for animal donation were similar to those obtained with human organs, & if both options are available for transplant, all participants said they would prefer an organ from human being. Given the preference, 70% preferred cadaver donors as compared to 20% and 10% who were in favour of live related human donation and xenotransplantation respectively. 80% had no idea about whether their religion allows for organ donation or not. 60% participants said that they would not prefer xenotransplan if it puts life of animal donor in danger. 95% participants were in favour of continued research in the field of xenotransplantation. 40% of participants believed that xenotransplantation is against the law of Nature/God. Conclusion: In the population studied, a positive attitude toward xenotransplantation was seen, although if given options, participants preferred organs from human being. Positive atitiude among participants was seen regarding further research in the field of xenotransplantation.